Sex Differences in Insular Cortex Gyri Responses to the Valsalva Maneuver - Macey, Paul M.; Rieken, Nicholas S.; Kumar, Rajesh; Ogren, Jennifer A.; Middlekauff, Holly R.; Wu, Paula; Woo, Mary A.; Harper, Ronald M. (Frontiers in Neurology, 2016)
Sex differences in autonomic regulation may underlie cardiovascular disease variations between females and males. One key autonomic brain region is the insular cortex, which typically consists of five main gyri in each hemisphere, and shows a topographical organization of autonomic function across those gyri. The present study aims to identify possible sex differences in organization of autonomic function in the insula. We studied brain functional magnetic resonance imaging (fMRI) responses to a series of four 18 sec Valsalva maneuvers in 22 healthy females (age±std: 50.0±7.9 yrs), and 36 healthy males (45.3±9.2yrs). Comparisons of heart rate and fMRI signals were performed with repeated measures ANOVA (threshold P<0.05 for all findings). All subjects achieved the target 30mmHg expiratory pressure for all challenges. Typical heart rate responses were elicited by the maneuver, including heart rate increases from approximately 4 seconds into the strain period (Phase II) and rapid declines to below baseline 5-10 seconds following strain release (Phase IV). Small but significant sex differences in heart rate percent change occurred during the sympathetic-dominant Phase II (female<male), and parasympathetic-dominant Phase IV (female>male, i.e., greater undershoot in males). The insular cortices showed similar patterns in all gyri, with greater signal decreases in males than females. Both sexes exhibited an anterior-posterior topographical organization of insular responses during Phase II, with anterior gyri showing higher responses than more posterior gyri. The exception was the right anterior-most gyrus in females, which had lower responses than the four other right gyri. Responses were lateralized, with right-sided dominance during Phase II in both sexes, except the right anterior-most gyrus in females, which showed lower responses than the left. The findings confirm the anterior and right-sided sympathetic dominance of the insula. Although sex differences were prominent in response magnitude, organization differences between males and females were limited to the right anterior-most gyrus, which showed a lower fMRI response in females vs. males (and vs. other gyri in females). The sex differences suggest a possible differing baseline state of brain physiology or tonic functional activity between females and males, especially in the right anterior-most gyrus.